We want to help: ethical challenges of medical migration and brain waste during a pandemic - Fenton, Elizabeth (Journal of medical ethics, 2023)
Health worker shortages in many countries are reaching crisis levels, exacerbated by factors associated with the COVID-19 pandemic. In New Zealand, the medical specialists union has called for a health workforce emergency to be declared, yet at the same time, many foreign-trained healthcare workers are unable to stay in the country or unable to work. While their health systems differ, countries such as New Zealand, the USA and the UK at least partially rely on international medical graduates (IMGs) to ensure access to health services, particularly in underserved communities. This paper focuses on the challenges faced by many IMGs, particularly those that constrain their capacity to live and work in the countries that rely on their skills. These challenges give rise to two ethical problems. First, they represent a failure of reciprocity towards IMGs; second, they represent a source of harm, both to IMGs themselves and to communities whose healthcare service depends on contributions made by IMGs. We argue that brain waste and disvaluing the contributions of IMGs and other foreign-trained health professionals have significant costs for maintaining a functional healthcare system, costs which must be adequately recognised and counted.